3D printing of toughened enantiomeric PLA/PBAT/PMMA quaternary system with complete stereo-complexation: Compatibilizer architecture effects. (1st March 2022) - Yang, Jing; Li, Wei; Mu, Bingnan; Xu, Helan; Hou, Xiuliang; Yang, Yiqi
Abstract: A novel toughening technique for 3D printed completely stereo-complexed PLA was devised. Stereo-complexation improves heat and hydrolysis resistance of traditional PLA but intensify its brittleness. Though PBAT elastomer with non-reactive compatibilizer PMMA enhances toughness of traditional PLLA, effects of the two components on crystalline structures and thus heat and hydrolysis resistance of stereo-complexed PLA kept unknown. To add to the challenge, technical difficulties occurred when trying to make stereo-complexation and controlled dispersion of PBAT in the enantiomeric PLA/PBAT/PMMA quaternary system adaptive to 3D printing. The hypothesis is that controlled compatibilization effect of PMMA endows PBAT with good dispersibility in the quaternary system, without affecting the hierarchical crystallization of enantiomeric PLA matrices for complete stereo-complexation. To analyze compatibilization effect of PMMA, interfacial, viscoelastic, crystalline, thermal, thermodynamical, mechanical, and rheological properties were systematically studied. Such a technique provides a new and facile solution to manufacture high-performance 3D printed PLA matrix. Graphical abstract: Image 1 Highlights: Strategy adaptive to 3D printing of toughened stereo-complexed PLA was designed. Controlled compatibilization of PMMA determined the toughening effect. Controlled compatibilization did not affect hierarchical crystallization of sc-PLA. Effects of compatibilization effect on PLA properties were systematically studied. 100% sc-level and high toughness was achieved in 3D printed PLA matrices.